Impact of Product Quality and Brand Image Towards Buying Decisions with Buying Interest as Mediation Variable - Wenty Febrianti; Rifqi Hasan (Publikasi Indonesia, 2022)
This research was conducted to find out empirical evidence of the role of buying interest in mediating product quality and brand image on purchasing decisions in the millennial generation in the Central Jakarta area, there is the online shop Matahari.com. The analysis method in this study uses structural equation modeling (SEM), sample of 225 respondents, the sampling technique refers to the calculation of Hair which is used for research with SEM analysis. The results showed that 1) Product quality had a positive and significant effect on buying interest, 2) Brand image had a positive and significant effect on buying interest. 3) Product quality has a positive and significant effect on buying decisions. 4) Brand image has a positive and significant effect on buying decisions. 5) buying interest has a positive and significant effect on buying decisions. 6) Product quality has a positive and significant effect on buying decisions through buying interest. 7) Brand image has a positive and significant effect on buying decisions through buying interest. So that in order to increase consumer buying interest in order to improve buying decisions, Matahari management needs to maintain product quality and brand image of Matahari.com, Matahari must continue to innovate both in terms of quality control through product specifications and pay attention to reviews from consumers, and control suppliers so as to create brand loyalty. in the eyes of consumers and always prioritizes technology in all promotional activities, especially to attract the millennial generation. The novelty of this research is to measure indicators per dimension of exogenous and endogenous variables by collaborating with mediating variables through structural equation modeling (SEM) data analysis.